1998
DOI: 10.1007/s003300050402
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the brain using the fast-spin-echo and gradient-spin-echo techniques

Abstract: The aim of our study was to compare gradient-spin-echo (GRASE) to fast-spin-echo (FSE) sequences for fast T2-weighted MR imaging of the brain. Thirty-one patients with high-signal-intensity lesions on T2-weighted images were examined on a 1.5-T MR system. The FSE and GRASE sequences with identical sequence parameters were obtained and compared side by side. Image assessment criteria included lesion conspicuity, contrast between different types of normal tissue, and image artifacts. In addition, signal-to-noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…By acquiring multiple gradient echoes per refocusing pulse on either side of the spin echo, an accelerated acquisition trajectory may be realized which exhibits pure T 2 weighting in the k-space centre (spin echo signal) and T 2 ⁎ weighting in the k-space periphery (gradient echo signal). Some researchers reported that GRASE was less effective in the detection of small or hypointense lesions (Patel et al, 1995;Umek et al, 1998), and produced images with lower signal to noise ratio (SNR) and less pronounced contrast (Fellner et al, 1995(Fellner et al, , 1997. However, others found that GRASE showed better detection of lesions, especially those with low signal (Melhelm et al, 1998) or those which exhibited paramagnetic susceptibility characteristics (Rockwell et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…By acquiring multiple gradient echoes per refocusing pulse on either side of the spin echo, an accelerated acquisition trajectory may be realized which exhibits pure T 2 weighting in the k-space centre (spin echo signal) and T 2 ⁎ weighting in the k-space periphery (gradient echo signal). Some researchers reported that GRASE was less effective in the detection of small or hypointense lesions (Patel et al, 1995;Umek et al, 1998), and produced images with lower signal to noise ratio (SNR) and less pronounced contrast (Fellner et al, 1995(Fellner et al, , 1997. However, others found that GRASE showed better detection of lesions, especially those with low signal (Melhelm et al, 1998) or those which exhibited paramagnetic susceptibility characteristics (Rockwell et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…A combined gradient and spin echo sequence known as gradient and spin echo (GRASE) (Feinberg and Oshio, 1991) has previously been used to accelerate clinical MR acquisitions (Fellner et al, 1995(Fellner et al, , 1997Melhelm et al, 1998;Patel et al, 1995;Rockwell et al, 1997;Umek et al, 1998). By acquiring multiple gradient echoes per refocusing pulse on either side of the spin echo, an accelerated acquisition trajectory may be realized which exhibits pure T 2 weighting in the k-space centre (spin echo signal) and T 2 ⁎ weighting in the k-space periphery (gradient echo signal).…”
Section: Introductionmentioning
confidence: 99%
“…At lower magnetic strength, GRASE imaging was shown to reduce scan time for brain imaging and to have potential for clinical use in patients with brain disorders …”
Section: Discussionmentioning
confidence: 99%
“…Recent reports comparing the performance of TSE and GRASE are slightly discouraging, claiming that TSE is more consistent in image quality, showing fewer artifacts [177]. Recent reports comparing the performance of TSE and GRASE are slightly discouraging, claiming that TSE is more consistent in image quality, showing fewer artifacts [177].…”
Section: Gradient-and Spin-echo Techniquesmentioning
confidence: 99%